Decision Support System for Rooftop Solar in the Bronx. - Katsamakas, E.
This paper proposes a decision support system for the economic and technical feasibility of operating distributed photovoltaics in Bronx, N.Y. Existing research shows that distributed generation (DG) is a more effective way of reengineering the electricity system to integrate more renewable sources compared to a centralized, fossil fuel-based system. The viability of decentralizing electricity production with solar, however, is location-dependent and does not achieve the economies of scale that centralized systems enjoy. To determine the economic feasibility of DG with photovoltaics at a regional level, the system proposed here accounts for the relative cost to consumers and supply of electricity from the grid based on a framework developed by the National Renewable Energy Laboratory. The variables that were considered include regional demand, space capacity, fixed and variable costs to consumers, supply costs, and existing government support programs. Thus, drawing on data reported by the New York City government and other sources, this paper found that rooftop solar is economically feasible with existing government support programs and can reduce overall emissions despite being unable to meet the Bronx?s peak demand. The proposed system can therefore be adopted and used by public and/or private local decision-makers from other similar locations.